English Language Analysis In Sales Marketing Through Live Streaming Method To Enhance Banyuwangi's Traditional Batik MSMEs - Khoiruman, Muhamad Alfi; Irawan, Doni Hadi (UNIVERSITAS PAKUAN, 2025)
The rapid development of digital technology has changed marketing strategies worldwide, including in Indonesia. One growing trend is the use of live streaming, which has become an effective tool for micro, small, and medium enterprises (MSMEs). This study explores how English is strategically used in live-streamed sales to support Banyuwangi’s traditional batik MSMEs. Using a mixed methods approach, the research combines qualitative analysis of language use and quantitative evaluation of marketing performance. Data were collected through observing live streaming sessions, interviewing business owners and hosts, and analyzing engagement and sales metrics. The results show that English phrases such as “limited offer,” “buy one get one,” and “check out now” are used to build urgency and emotional connection. The use of both English and Indonesian (code-switching) helps increase audience engagement, improves brand image, and adds a sense of professionalism. Quantitative findings indicate a 17–24% increase in sales within 24 hours after sessions using mixed language strategies. However, some hosts face challenges such as mispronunciation and lack of confidence, suggesting the need for practical English training. This study concludes that English is not only a communication tool but also a symbol of modern branding and global readiness. The findings provide useful insights for empowering MSMEs and contribute to business linguistics, emphasizing the importance of language in digital marketing.